Mechanical, tribological and fractography analysis of structural grade Al7075/n-TiC composites and optimization of wire EDM parameters through Taguchi method (Fracture and Structural Integrity, 2026)
The effects of nanoscale TiC (n-TiC) reinforcement on Al7075 composites made by stir casting with 0%, 1%, 2%, 3%, and 4% reinforcement are examined in this work. The existence of n-TiC particles in the aluminum matrix was verified by microstructural investigation. When compared to un-reinforced alloy (Al7075), the mechanical, tribological, and wear properties were greatly improved by the addition of n-TiC; hardness, tensile strength, and wear resistance increased by 28.57%, 24.41%, and 33.69%, respectively. Molybdenum wire was used as the electrode material in an experimental investigation of the produced nano composites' machinability characteristics during Wire Electrical Discharge Machining (WEDM). Two machining attributes, Material Removal Rate (MRR) and Surface Roughness (SR), are examined in connection to the combinational values of pulse time ON, pause time OFF, as well as peak current, which are chosen as the changeable input process elements. The results of the experiment showed that as pulse on time and peak current levels increased, so did MRR and Ra values. Under these circumstances, the wire electrode has maximum current, which makes it simple to remove more material and produce a moderate surface finish. The ANOVA results show that the "Pulse ON Time" has the biggest impact (47.01 %) on MRR and 36.64% impact on surface roughness values compared to the other factors, making it the most important parameter. The confirmatory test results revealed that the errors in MRR and Ra values were within acceptable limits. In the present research work, Taguchi methods have been successfully implemented to identify the optimum machining conditions for Al7075/n-TiC composites.
Keywords: Al7075; n-TiC; Micro-structure; Mechanical; Wear; Fracture Surface; Wire EDM; Taguchi